Capacidade de força dos membros superiores em competidores de montaria em touros - Souza, Arthur Bertagia de [UNESP]; Verardi, Carlos Eduardo Lopes [UNESP]; Neiva, Cassiano Merussi [UNESP]; Pessôa Filho, Dalton Müller [UNESP] (My University, 2011)
This study did evaluate the handgrip strength capacity of bull riding practitioners and recreational practitioners in order to obtain parameters of the muscular fitness of subjects undertaken this sports practice. Twenty right-handed subjects were grouped into bull riding athletes (10 individuals at AMT: 174.5 ± 5.2 cm of height, 78.9 ± 12 kg of body weight, 24.7 ± 6.1 years, and 13,8 ± 2.4% for body fat) and non-athletes (10 subjects n-AMR: 178.5 ± 7.3 cm of height, 81.2 ± 8.8kg of body weight, 21.7 ± 2.3 years, and 13.8 ± 1.9% of body fat). They were underwent to protocols of handgrip strength evaluation by a standard and specific dynamometry (simulating a bull riding posture) of right (DPD e DED) e left (DEP e DEE) hands. The dynamic force values from one repetition to maximum test (1RM) were either obtained in conventional load-based system for upper limbs exercises. The values were compared by the test-t for independent data, assuming ρ ≤ 0.05. The relationship between the values of strength from handgrip and dynamic exercises were drawn by Pearson correlation. The results of the AMT to DPD (43.8 ± 6.8kgf), DPE (39.4 ± 7.7kgf), DED (44.9 ± 5.6kgf), and DEE (39.8 ± 8.3kgf). For the n-AMT in DPD (47.0 ± 3.0kgf), DPE (42.2 ± 6.1kgf), DED (49.2 ± 1.5kgf), and DEE (46.2 ± 4.1kgf). Significant difference was observed between DED and DEE. The strength tests of 1RM at bench press (73.2 ± 12.0kg and 82.0 ± 12.0kg), arm-curl (45.2 ± 8.9kg and 43.8 ± 8.9kg), triceps pulley (67.0 ± 6.3kg and 72.0 ± 6.3kg), and pulley (73.5 ± 8.5kg and 73.7 ± 7.5kg) for groups n-AMT and AMT did not showed differences. Correlations were showed between all handgrip tests and elbow flexor force for AMT, and between DPD and elbow extensor, abductor, adductor and extensor of shoulder for n-AMT. influences to the performance of the force dynamometry. It could be concluded that handgrip force and dynamic strength of upper limbs did not were putative responses for bull riding practice.

Este estudo avaliou a preensão manual de praticantes e não praticantes de montaria em touros para obter parâmetros de referência da aptidão de força destes sujeitos. Vinte sujeitos, divididos em dois grupos, 10 atletas de montaria em touros (AMT: 174,5 ± 5,2 cm de estatura, 78,9 ± 12 kg de peso corporal, 24,7 ± 6,1 anos e 13,8 ± 2,4% de gordura corporal) e 10 não atletas de montaria em touros (nAMT: 178,5 ± 7,3 cm de altura, 81,2 ± 8,8 kg de peso corporal, 21,7 ± 2,3 anos e 13,8 ± 1,9% de gordura corporal) foram submetidos aos protocolos de avaliação da força de preensão manual em dinamômetria padrão e específica (simulando uma postura de montaria) para os braços direito (DPD e DED) e esquerdo (DPE e DEE), bem como a avaliação da força máxima dinâmica dos membros superiores em aparelhos convencionais de exercícios com pesos. As médias das variáveis analisadas foram comparadas pelo teste-t para dados independentes, adotando-se nível de significância em ρ ≤ 0,05. As relações entre os valores de força e preensão manual e dinâmica foram traçadas pelo coeficiente de Pearson. Os resultados para AMT na DPD (43,8 ± 6,8kgf), DPE (39,4 ± 7,7kgf), DED (44,9 ± 5,6kgf) e DEE (39,8 ± 8,3kgf), quando comparados aos valores apresentados por n-AMT na DPD (47,0 ± 3.0kgf), DPE (42,2 ± 6,1kgf), DED (49,2 ± 1,5kgf) e DEE (46,2 ± 4,1kgf), apresentaram diferenças apenas para DED e DEE. A força no teste de 1RM no supino reto (73,2 ± 12,0kg e 82,0 ± 12,0kg), rosca direta (45,2 ± 8,9kg e 43,8 ± 8,9kg), tríceps pulley (67,0 ± 6,3kg e 72,0 ± 6,3kg) e puxada posterior (73,5 ± 8,5kg e 73,7 ± 7,5kg) para os grupos AMT e n-AMT, não evidenciaram diferenças. A influência sobre a preensão manual foi apresentada pelos flexores do cotovelo em todas as variações da dinamometria realizadas em AMT, e pelos extensores do cotovelo, adutores, abdutores e extensores do ombro na DPD em nAMT. Conclui-se que a força de empunhadura e a força dinâmica dos membros superiores não são respostas adaptativas da prática de montaria em touros.
Upper-limbs strength of bull riding competitors
Keywords: Handgrip strength; Dynamic force; Anthropometry; Bull riding; Preensão manual; Força dinâmica; Antropometria; Montaria em touro